Anesthesia management of complete versus incomplete placenta previa: a retrospective cohort study. (3rd May 2018) - Orbach-Zinger, Sharon; Weiniger, Carolyn F.; Aviram, Amir; Balla, Alexander; Fein, Shai; Eidelman, Leonid A.; Ioscovich, Alexander
Abstract: Purpose: Placenta previa (PP) is a major cause of obstetric hemorrhage. Clinical diagnosis of complete versus incomplete PP has a significant impact on the peripartum outcome. Our study objective is to examine whether distinction between PP classifications effect anesthetic management. Methods and materials: This multi-center, retrospective, cohort study was performed in two tertiary university-affiliated medical centers between the years 2005 and 2013. Electronic delivery databases were reviewed for demographic, anesthetic, obstetric hemorrhage, and postoperative outcomes for all cases. Results: Throughout the study period 452 cases of PP were documented. We found 134 women (29.6%) had a complete PP and 318 (70.4%) had incomplete PP. Our main findings were that women with complete PP intraoperatively had higher incidence of general anesthesia ( p  = .017), higher mean estimated blood loss ( p  < .001), increased blood components transfusions ( p  < .001), and significant increase in cesarean hysterectomy rate ( p  < .001) than women with incomplete PP. Additionally, complete PP was associated with more postoperative complications: higher incidence of admission to the intensive care unit (ICU) ( p  < .001), more mechanical ventilation ( p  = .02), a longer median postoperative care unit (PACU) ( p  = .02), ICU ( p  = .002), and overall length of stay in the hospital ( p  < .001). Conclusions: Complete PP is associated with increased risk of hemorrhage compared with incomplete PP. Therefore distinction between classifications should be factored into anesthetic management protocols.